Analytical study of carriers in silicon nanowires - Ahmadi, Mohammad Taghi (2009)
The limitations on carrier (holes and electrons) drift due to high-field streamlining also randomly velocity vector in equilibrium is reported. Asymmetrical distribution function that converts randomness in zero-field to streamlined one in a very high electric field is employed. The ultimate drift velocity is found to be appropriate thermal velocity for a given dimensionality for non-degenerately doped nanostructure. However, the ultimate drift velocity is the Fermi velocity for degenerately doped nanostructures. Quantum and high-field effects controlling the transport of carrier in nanostructures are described. The results obtained are applied to the modeling of a nanowire transistor